2022
DOI: 10.3390/ijms23042118
|View full text |Cite
|
Sign up to set email alerts
|

Actin-Associated Proteins and Small Molecules Targeting the Actin Cytoskeleton

Jing Gao,
Fumihiko Nakamura

Abstract: Actin-associated proteins (AAPs) act on monomeric globular actin (G-actin) and polymerized filamentous actin (F-actin) to regulate their dynamics and architectures which ultimately control cell movement, shape change, division; organelle localization and trafficking. Actin-binding proteins (ABPs) are a subset of AAPs. Since actin was discovered as a myosin-activating protein (hence named actin) in 1942, the protein has also been found to be expressed in non-muscle cells, and numerous AAPs continue to be discov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 132 publications
1
35
0
Order By: Relevance
“…After the exit of Pi, ADP-bound F-actin represents the 'aged' state of the filament, which can then be depolymerized back to G-actin. In vivo, this cyclic process is tightly regulated by a wide variety of actin-binding proteins (ABPs) that control the kinetics of actin turnover [8][9][10] . For instance, Gactin probably does not exist at significant concentrations as the uncomplexed monomer in vivo; instead it is essentially always bound to ABPs such as profilin and thymosin-b4 to prevent uncontrolled nucleation events 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…After the exit of Pi, ADP-bound F-actin represents the 'aged' state of the filament, which can then be depolymerized back to G-actin. In vivo, this cyclic process is tightly regulated by a wide variety of actin-binding proteins (ABPs) that control the kinetics of actin turnover [8][9][10] . For instance, Gactin probably does not exist at significant concentrations as the uncomplexed monomer in vivo; instead it is essentially always bound to ABPs such as profilin and thymosin-b4 to prevent uncontrolled nucleation events 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have shown that there is an inverse relationship between actin polymerization and adipogenesis, whereas there is a direct correlation between actin polymerization and osteogenesis [27,28,[42][43][44]. The dynamic nature of the actin cytoskeleton is determined by the actions of numerous actin-binding proteins, such as cofilin, profilin, CapZ, Arp2/ 3, and Ena/VASP family [45][46][47]. EVL, one of the Ena/VASP family involved in actin assembly and elongation, has been implicated in several types of cells with cell proliferation and differentiation by enhancing actin polymerization [37,39,[48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…In the attenuated strain of H. meleagridis, the most prominent category of upregulated surface-associated proteins is cytoskeleton proteins, representing over one-third of the upregulated proteins in that strain. Comprising actin-related, actin-like and actin-associated proteins (AAPs) such as coronin, fibrin, and alpha-actinin, their action is focused in cytoskeleton remodeling and rearrangements [ 70 ]. It has been shown that these proteins are involved in the dynamic remodeling of the actin cytoskeleton, playing a role in multiple physiological processes such as cell migration, endocytosis, cytokinesis and cell morphogenesis [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Comprising actin-related, actin-like and actin-associated proteins (AAPs) such as coronin, fibrin, and alpha-actinin, their action is focused in cytoskeleton remodeling and rearrangements [ 70 ]. It has been shown that these proteins are involved in the dynamic remodeling of the actin cytoskeleton, playing a role in multiple physiological processes such as cell migration, endocytosis, cytokinesis and cell morphogenesis [ 70 , 71 ]. In agreement with this, attenuated histomonads demonstrate an amoeboid cellular morphology in vitro [ 72 ].…”
Section: Discussionmentioning
confidence: 99%